Management of cyclic vomiting syndrome in adults: Evidence review. (26th June 2019) - Sharaf, Ravi N.; Venkatesan, Thangam; Shah, Raj; Levinthal, David J.; Tarbell, Sally E.; Jaradeh, Safwan S.; Hasler, William L.; Issenman, Robert M.; Adams, Kathleen A.; Sarosiek, Irene; Stave, Christopher D.; Li, B U. K.; et al.
Abstract: Background: This evidence review was conducted to inform the accompanying clinical practice guideline on the management of cyclic vomiting syndrome (CVS) in adults. Methods: We followed the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework and focused on interventions aimed at prophylactic management and abortive treatment of adults with CVS. Specifically, this evidence review addresses the following clinical questions: (a) Should the following pharmacologic agents be used for prophylaxis of CVS: amitriptyline, topiramate, aprepitant, zonisamide/levetiracetam, or mitochondrial supplements? (b) Should the following pharmacologic agents be used for abortive treatment: triptans or aprepitant? Results: We found very low_quality evidence to support the use of the following agents for prophylactic and abortive treatment of CVS: amitriptyline, topiramate, aprepitant, zonisamide/levetiracetam, and mitochondrial supplements. We have moderate certainty of evidence for the use of triptans as abortive therapy. We found limited evidence to support the use of ondansetron and the treatment of co_morbid conditions and complementary therapies. Conclusions: This evidence review helps inform the accompanying guideline for the management of adults with CVS which is aimed at helping clinicians, patients, and policymakers, and should improve patient outcomes.